Resource Utilization in Children With Tuberous Sclerosis Complex and Associated Seizures: A Retrospective Chart Review Study. (April 2013) - Lennert, Barb; Farrelly, Eileen; Sacco, Patricia; Pira, Geraldine; Frost, Michael
Seizures are a hallmark manifestation of tuberous sclerosis complex, yet data characterizing resource utilization are lacking. This retrospective chart review was performed to assess the economic burden of tuberous sclerosis complex with neurologic manifestations. Demographic and resource utilization data were collected for 95 patients for up to 5 years after tuberous sclerosis complex diagnosis. Mean age at diagnosis was 3.1 years, with complex partial and infantile spasms as the most common seizure types. In the first 5 years post-diagnosis, 83.2% required hospitalization, 30.5% underwent surgery, and the majority of patients (90.5%) underwent ≥3 testing procedures. In 79 patients with a full 5 years of data, hospitalizations, intensive care unit stays, diagnostic testing, and rehabilitation services decreased over the 5-year period. Resource utilization is cost-intensive in children with tuberous sclerosis complex and associated seizures during the first few years following diagnosis. Improving seizure control and reducing health care costs in this population remain unmet needs.